Judicial review of revenue authority decisions in a specific tax treaty context – a study of the extent of convergence in the reasoning of different courts reviewing revenue authority decisions under model-based tax treaties - van Rensburg, Liesl Nicola (Department of Commercial Law, 2022)
This minor dissertation analyses how different courts review the exercise of discretion under specific model-based tax treaty clauses that confer wide decision-making powers to officials. The aim is to identify whether there is convergence in argument that may be of relevance to other courts for the uniform interpretation of tax treaties. The research methodology adopted in this dissertation is doctrinal research. It was conducted primarily through foreign case law sourced from the International Tax Law Reports and the International Bureau of Fiscal Documentation. It is concluded in this minor dissertation that there is evidence of convergence on the justiciability of requests for the cross-border exchange of taxpayer information. The courts are recognising the principle of legality with differences in their approach to judicial review. There is an extent of convergence in respect of the interpretation of the standard of foreseeable relevance as condition to legality in this context, with most courts applying a deferential approach. There is also evidence of convergence in relation to confidentiality provisions with the courts applying principles of procedural fairness with slight divergence on issues of disclosure. It is not possible at this stage to determine convergence in respect of the model-based mutual agreement procedure and principal purpose test. Case law analysed in these contexts are however instructive and provide arguments that may be of value to other courts.